2022
DOI: 10.1021/acs.jpclett.2c00229
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Restricting Intermolecular Vibration of a Herringbone Dimer for Significantly Enhanced Multicolor Emission in Rotor-Free Truxene Crystals

Abstract: Organic solid-state luminescent materials exhibit numerous exciting photoelectric properties that are central to emergent organic light-emitting diodes, smart sensors, and data encryption. However, the luminescence of pure organic rotor-free materials has been afflicted with strong intermolecular π−π stacking interactions. Herein, an unprecedented pressureinduced emission enhancement (PIEE) is realized in a system of rigid planar pure polycyclic aromatics, i.e., truxene crystals. The emission intensity is enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Then, the PL intensity started to decrease with pressure until the PL disappeared completely upon 16.5 GPa (Figure S6). This phenomenon indicated that the enhancement of the π–π interaction played a leading role in the weakening of PL intensity [18] . During the decompression process, a remarkable emission increasement appeared and pressure‐treated Tb(BTC)(H 2 O) 6 showed a monochromatic emission enhancement (Figure 2b,c).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Then, the PL intensity started to decrease with pressure until the PL disappeared completely upon 16.5 GPa (Figure S6). This phenomenon indicated that the enhancement of the π–π interaction played a leading role in the weakening of PL intensity [18] . During the decompression process, a remarkable emission increasement appeared and pressure‐treated Tb(BTC)(H 2 O) 6 showed a monochromatic emission enhancement (Figure 2b,c).…”
Section: Resultsmentioning
confidence: 88%
“…This phenomenon indicated that the enhancement of the π-π interaction played a leading role in the weakening of PL intensity. [18] During the decompression process, a remarkable emission increasement appeared and pressure-treated Tb(BTC)(H 2 O) 6 showed a monochromatic emission enhancement (Figure 2b,c). It is suggested that the energy levels of S 1 and T 1 after pressure treatment were close to the metal ions, thereby enhancing the PL intensity by improving the efficiency of LMET.…”
Section: Resultsmentioning
confidence: 95%
“…[13][14][15][16] In particular, organic molecular crystals with weak intermolecular interactions, such as van der Waals forces, hydrogen bonding, charge transfer, etc., have been attracting intensive research interest in this field, in which πconjugated molecules are commonly used as building blocks due to their unique optical and electronic properties combined with their high sensitivity to the environment. [17][18][19] According to the tight binding model, compression induced strengthening of intermolecular interactions could widen energy bands and thus reduce the energy gap, 20 while the enhanced interactions such as π-π interaction, could also lead to emission quenching. 21 Therefore, most luminescent materials known so far show a gradually red-shifted and quenched emission upon compression.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the pressure-induced emission enhancement (PIEE) phenomenon was discovered in many systems. Zou et al found that tetraphenylethene shows PIEE with an extra pressure in the range of 1.5 to 5.3 GPa owing to the enhanced intermolecular C–H···π and C–H···C interactions . PIEE is also observed in a rotor-free truxene crystal because of the effective restriction of the intermolecular vibration of dimers packed in herringbone . The perylene-1,2,4,5-tetracyanobezene cocrystal exhibits blue-shifted and enhanced emission upon compression within 3 GPa due to the tailored donor–acceptor interactions by inserting tetrahydrofuran molecules .…”
Section: Introductionmentioning
confidence: 99%
“…22 PIEE is also observed in a rotor-free truxene crystal because of the effective restriction of the intermolecular vibration of dimers packed in herringbone. 23 The perylene-1,2,4,5-tetracyanobezene cocrystal exhibits blueshifted and enhanced emission upon compression within 3 GPa due to the tailored donor−acceptor interactions by inserting tetrahydrofuran molecules. 24 Thus, the pressureresponsive photophysical properties of organic luminescent materials are complex and highly system-dependent.…”
Section: ■ Introductionmentioning
confidence: 99%